The Role of English as a Second Language in the Acquisition of Indonesian as a Third Language - A. Qodir Sanusi; Indra Darmawan (IJBLE Scientific Publications Community Inc., 2026)
Cross-linguistic influence in third language (L3) acquisition is closely related to both first language (L1) and second language (L2) acquisition. This study investigates the role of English as an L2 in the acquisition of Indonesian as an L3, with particular attention to two aspects: (1) the role of English in articulation and (2) the role of English as a vocabulary provider. Employing a qualitative research design, the data were collected through face-to-face conversations and picture-based sentence production tasks involving three BIPA (Bahasa Indonesia bagi Penutur Asing) students from Thailand and Madagascar. The findings indicate that English performs two principal functions. First, it supports learners in mastering sounds that are absent from their L1, while at the same time influencing their Indonesian pronunciation patterns. Second, English functions as a bridge language or supplier language when learners do not yet possess specific lexical items in Indonesian, as evidenced by both adapted and unadapted lexical transfers. These findings contribute to a broader understanding of multilingual acquisition processes and offer practical implications for BIPA instruction.